NON-CYCLIC ECONOMIC CRISIS OF UKRAINE BETWEEN 2013 AND 2015: CAUSES AND REMEDIES - Orel Yu.L. (Pressing Problems of Public Administration, 2015)
The author proves a necessity for theoretical aspects of economic cycles, set the main causes ofthe crisis in the economy of Ukraine in the period from 2013 to 2015, found conditions that contributedto the onset of the crisis, suggested priority areas to overcome the negative effects of the crisis.